Effect of Ferula gummosa Ethanolic Extract on Osteogenesis in Human Mesenchymal Stem Cells - Z Mahmoudi; M Soleimani; A Saidi; M Iranshahi; A Azizsoltanli (Institue of Medicinal Plants, ACECR, 2013)
Background: Osteoporosis is one of the most prevalent deasese in current century .Estrogen deficiency is the basic cause of osteoporosis in menopaused women. Hormone Replacement Therapy (HRT) can increase the risk of breast and ovary cancers. Medicinal plant are natural source of secondary metabolite and can a reliable source for treating osteoporosis. Ferula gummosa (Galbanum) has been used in traditional medicine since ancient time. Objective: This study is focused on determining the effect of Galbanum root ethanolic extract on osteogenesis progress in Human Mesenchymal Stem Cells (hMSCs). Methods: The Bone Marrow hMSCs were seeded at 12 well plates and treated with different amount of Galbanum extracts (0.5 to 100µg/ml). Extract cytotoxicity were measured using MTT method .Effect of extract on osteogenesis was evaluated in time interval 7 and 14 days using_ Alkaline Phosphatase_ enzyme activity method. Results: The data analysis revealed a significant increase in cell proliferation in range of (0.5 to 5) µg/ml after 24, 48 and 72 hour of treatment with galbanum extract. Analysis of result revealed a significant increase in alkaline phosphatase (ALP) enzyme activity in the range of 1 to 10 µg/ml compared with control group. Conclusion: Ferula gumossa has been used in Iranian folk medicine for many years. Our in vitro study showed that Frula gummosa extract has osteoprotective effect.